Cost utility of fractional exhaled nitric oxide monitoring for the management of children asthma (2021)
ABSTRACT: Introduction: Fractional exhaled nitric oxide is a simple, non-invasive measurement of airway inflammation with minimal discomfort to the patient and with results available within a few minutes. This study aimed to evaluate the cost-effectiveness of asthma management using fractional exhaled nitric oxide monitoring in patients between 4 and 18 years of age. Methods: A Markov model was used to estimate the cost-utility of asthma management using fractional exhaled nitric oxide monitoring versus asthma management without using fractional exhaled nitric oxide monitoring (standard therapy) in patients between 4 and 18 years of age. Cost data were obtained from a retrospective study on asthma from a tertiary center, in Medellin, Colombia, while probabilities of the Markov model and utilities were obtained from the systematic review of published randomized clinical trials. The analysis was carried out from a societal perspective. Results: The model showed that fractional exhaled nitric oxide monitoring was associated with a lower total cost than standard therapy (US $1333 vs. US $1452 average cost per patient) and higher QALYs (0.93 vs. 0.92 average per patient). The probability that fractional exhaled nitric oxide monitoring provides a more cost-effective use of resources compared with standard therapy exceeds 99% for all willingness-to-pay thresholds. Conclusion: Asthma management using fractional exhaled nitric oxide monitoring was cost-effective for treating patients between 4 and 18 years of age with mild to moderate allergic asthma. Our study suggests evidence that could be used by decision-makers to improve clinical practice guidelines, but this should be replicated in different clinical settings.